678.02.678.6 STUDY OF THE CONDITIONS FOR THE АMINOLYSIS OF SECONDАRY POLYCАRBONАTE: STUDY OF THE CONDITIONS FOR THE АMINOLYSIS OF SECONDАRY POLYCАRBONАTE - Yusupova, Malikaxon; Mаmаdjonovа, Mаxforа; Egаmberdiev, Sаhibjon; Abduvohidov, Iqboljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article investigates the aminolysis of secondary polycarbonate (IPC) (commonly found in car headlights, rims, polymer roofs, etc.) and monoethanolamine , (MEA) (GOST 10136-77 , produced in the Russian Federation) content of the main substance – 99.5%, density 1.12 g/cm 3The results of studying the aminolysis process with in the presence of a catalyst are presented. Catalyst as sodium hydroxide ( NaOH ) secondary polycarbonate ( IPC ) 1% was obtained . The main focus is on isolating urethane and phenolic compounds by performing a monoethanolamine (MEA) aminolysis process on secondary polycarbonate (IPC) and extracting the resulting product. This process was carried out in the ratio of secondary polycarbonate (IPC): monoethanolamine, (MEA) = 1:5 mol/unit . The duration of the aminolysis was carried out for a total of 6 hours at a temperature of 170 o C. The main physicochemical parameters of the resulting product and the results obtained based on infrared spectroscopy analysis are presented.